Λ-Shaped liquid crystal trimers with dual terminal cholesteryl moieties: synthesis and concomitant of N*, SmA and cholesteric glassy phases. Issue 2 (26th January 2018) - Ooi, Yew-Hong; Yeap, Guan-Yeow
ABSTRACT: Two homologous series of λ-shaped chiral liquid crystal trimers composed of a laterally substituted benzylidene-aniline as the central core armed by two cholestryl ester moieties via odd-even alkyl spacer are synthesised. All the compounds are mesogenic exhibiting both chiral nematic (N*) and SmA phases except for trimers bearing long spacers ( n  = 9–10). A pronounced odd-even effect is observed on the phase transition temperatures and clearing enthalpies when the spacer length is varied in which the even-parity members show higher value. The widening of N* phase upon elongation of the alkyl spacer can be interpreted as a result of the destabilisation of SmA phase. Full recrystallisation from the cholesteric phase upon cooling is not observed for all the compounds bearing long spacer, especially oxydecanoyl spacer. Instead, the anisotropic fluid vitrified to form the cholesteric glassy state characteristic of polymer at low temperature. This finding is also evident from the polarising optical microscope whereby non-crystalline texture which resembles the Grandjean texture with various reflection colours is observed upon cooling to low temperature. The effect of the lateral substituents on the liquid-crystalline behaviour is also discussed. Graphical Abstract: